Horka, a dominant mutation of Drosophila, induces nondisjunction and, through paternal effect, chromosome loss and genetic mosaics. - Szabad, J.; Mathe, E.; Puro, J. (Genetics, 1995)
Fs(3)Horka (Horka) was described as a dominant female-sterile mutation of Drosophila melanogaster. Genetic and cytological data show that Horka induces mostly equational nondisjunction during spermatogenesis but not chromosome loss and possesses a dominant paternal effect: the X, second, third and the fourth chromosomes, but not the Y, are rendered unstable while undergoing spermatogenesis and may be lost in the descending zygotes. The frequency of Horka-induced chromosome loss is usually 2-4% but varies with the genetic background and can be over 20%. The X chromosome loss occurs during the gonomeric and the initial cleavage divisions. Loss of the X and fourth chromosomes shows no correlation. We propose, based on similarities in the mutant phenotypes with the chromosome destabilizing mutations nonclaret disjunctional and paternal loss, that the normal Horka+ product is required for function of the centromeres and/or nearby regions. Horka is a convenient tool for the generation of gynandromorphs, autosome mosaics and for the study of gene expression in mosaics.